Penggunaan Gaya Bahasa Sarkasme pada Akun Instagram riaricis1795 - Robiyatul Adawiyah; Suwadi Suwadi; Ilmyatur Rosidah (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This research entitled "Use of Sarcasm on the riaricis1795 Instagram Account" aims to find the form of sarcasm used on riaricis1795's Instagram, especially on Instagram. Sarcasm is often used to convey sharp criticism, ridicule or sarcasm, which can influence the way of communication among social media users. This research refers to the use of sarcasm, stating that this style of language is not only intended to be sarcastic, but can also create a deep emotional impact. The method used in this research is descriptive qualitative, with data collection through note-taking techniques, listening techniques to posts and comments on the riaricis1795 Instagram account. The results of the analysis show that there are various forms of sarcasm that appear, including in the form of comments, captions, and interactions between users.